2021
DOI: 10.1002/aur.2586
|View full text |Cite
|
Sign up to set email alerts
|

Measurement invariance of the Childhood Autism Rating Scale (CARS) across six countries

Abstract: The Childhood Autism Rating Scale (CARS) is a simple and inexpensive tool for Autism spectrum disorder (ASD) assessments, with evidenced psychometric data from different countries. However, it is still unclear whether ASD symptoms are measured the same way across different societies and world regions with this tool, since data on its cross-cultural validity are lacking. This study evaluated the crosscultural measurement invariance of the CARS among children with ASD from six countries, for whom data were aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Marcus also discussed children’s communication behaviors in People Places: Design Guidelines for Urban Open Space, and divided children’s play behaviors in the urban built environment: observation-participation-avoidance-concealment [ 6 ]. However, due to regional differences, urban built environment impacts vary widely between developed and developing countries [ 7 ], and due to differences in cultural backgrounds, diagnoses of children with ASD in other countries may not provide cross-culturally valid results [ 8 ]. Therefore, this study uses the Autism Diagnostic Scale ( Table 1 ), which is suitable for China’s national conditions, as a reference and combines the Autism Children’s Development Assessment Scale ( Table 2 ) issued by the China Disabled Persons’ Federation to describe the play behavior of children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Marcus also discussed children’s communication behaviors in People Places: Design Guidelines for Urban Open Space, and divided children’s play behaviors in the urban built environment: observation-participation-avoidance-concealment [ 6 ]. However, due to regional differences, urban built environment impacts vary widely between developed and developing countries [ 7 ], and due to differences in cultural backgrounds, diagnoses of children with ASD in other countries may not provide cross-culturally valid results [ 8 ]. Therefore, this study uses the Autism Diagnostic Scale ( Table 1 ), which is suitable for China’s national conditions, as a reference and combines the Autism Children’s Development Assessment Scale ( Table 2 ) issued by the China Disabled Persons’ Federation to describe the play behavior of children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are indications that the GARS utilizes family, caregiver, and service provider inputs relevant to culturally and linguistically diverse populations [43]. Nevertheless, cultural/regional effects on its measurements may be reflected through variable levels of sensitivity and specificity across studies through some locally published non-English studies, such as Gorji et al [44], as reported when using other ASD scales [45], which may result in cross-cultural variability in ASD [2,46].…”
Section: Introductionmentioning
confidence: 99%
“…The CARS is a widely used diagnostic scale in China that has strong reliability and validity [ 25 27 ]. It consists of 15 items covering children’s social interaction, language, behavior and sensory aspects.…”
Section: Methodsmentioning
confidence: 99%